2023
DOI: 10.7759/cureus.36522
|View full text |Cite
|
Sign up to set email alerts
|

Chronomodulated Administration of Chemotherapy in Advanced Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: In this systematic review, the efficacy and safety of chronomodulated chemotherapy, defined as the delivery of chemotherapy timed according to the human circadian rhythm, were assessed and compared to continuous infusion chemotherapy for patients with advanced colorectal cancer.Electronic English-language studies published until October 2020 were searched. Randomised controlled trials (RCTs) comparing chronomodulated chemotherapy with non-chronomodulated (conventional) chemotherapy for the management of advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…On the contrary, a systematic review and meta-analysis of data from six randomized controlled trials involving 1347 patients on chronomodulated chemotherapies generally did not show any advantages over conventional therapies with regard to overall survival, objective response rate, or toxicity (Brenner et al, 2014;Huang et al, 2016) [4,184]. Other recent studies have confirmed these observations but found a reduction in hematologic toxicity in the chronomodulated therapy group (Nassar et al, 2023) [185]. Kinouchi and Sassone-Corsi (2020) [182] concluded that an information gap still exists regarding the existence of a common core clock connection between cancer and pluripotent stem cells that may elucidate the impact of the circadian clock on critical stages of cellular differentiation.…”
Section: Impact Of Circadian Rhythm On Crd Drug Delivery and Efficacymentioning
confidence: 96%
“…On the contrary, a systematic review and meta-analysis of data from six randomized controlled trials involving 1347 patients on chronomodulated chemotherapies generally did not show any advantages over conventional therapies with regard to overall survival, objective response rate, or toxicity (Brenner et al, 2014;Huang et al, 2016) [4,184]. Other recent studies have confirmed these observations but found a reduction in hematologic toxicity in the chronomodulated therapy group (Nassar et al, 2023) [185]. Kinouchi and Sassone-Corsi (2020) [182] concluded that an information gap still exists regarding the existence of a common core clock connection between cancer and pluripotent stem cells that may elucidate the impact of the circadian clock on critical stages of cellular differentiation.…”
Section: Impact Of Circadian Rhythm On Crd Drug Delivery and Efficacymentioning
confidence: 96%
“…A RCT come from America indicated that chronotype-tailored light therapy could significantly improve the life quality of breast cancer patients receiving adjunct therapies [89]. Many studies support the positive effect of chronotherapy in cancer management, while some researchers doubt about this opinion [90]. Thus, higher-quality studies are still needed to demonstrate the effectiveness of chronotherapy.…”
Section: Chronotherapy Perspectives In Tmementioning
confidence: 99%